Frequency of Acute Kidney Injury in Patients Admitted with Sepsis - Ehsan Ullah,; Kakar , Kaleemullah; Gulandam,; Gulzar , Mohammed Atif; Ahmed Babar , Shahzada Dawood; Afzal , Muhammad; Kakar , Sana Ullah (Indus Journal of Bioscience Research, 2025)
Background: When a patient is admitted with sepsis, acute kidney damage (AKI) is a frequent and dangerous consequence. It is linked to higher mortality, dialysis requirements, and morbidity. Objective: to evaluate the stages and clinical results of AKI and ascertain its prevalence in sepsis patients. Methods: A tertiary care hospital in Quetta hosted a six-month qualitative study. Purposive sample was used to select 130 septic patients in total. KDIGO criteria were used to diagnose AKI, and information was gathered from interviews and clinical records. Results: 49.2% of individuals with sepsis had AKI. The most prevalent stage of AKI was Stage 1 (39.1%), which was followed by Stage 2 (32.8%) and Stage 3 (28.1%). 12.5% of AKI patients passed away, 18.8% needed dialysis, and 43.8% recovered completely. Conclusion: This study reveals a high incidence of acute kidney injury (AKI) in sepsis patients, with 49.2% developing AKI. Men, middle-aged, and older individuals are more susceptible. The severity of septic AKI, including mortality and dialysis needs, significantly impacts prognosis. Early identification and intervention remain critical, as prompt treatment can prevent progression to advanced AKI stages. The findings suggest that conventional observation, early biomarkers, and personalized care are essential for better outcomes. Improved clinical practices can ultimately enhance survival rates and reduce complications in sepsis patients in critical care settings.